Modern techniques in cytopathology - Bui, Marilyn M.; Pantanowitz, Liron (Monographs in clinical cytology / series editor Philippe Vielh, 2020)
In the era of precision medicine, physicians are increasingly in need of more definitive diagnostic, prognostic, and predictive information derived from small biopsy specimens such as cytology samples in order to guide effective patient care. Cytopathology is well poised to meet this challenge. Whilst the traditional cytomorphologic component of cytology practice is still valid, enormous advances have been made in the field of cytopathology thanks to transformative technology and innovative individuals that have augmented the cytologists' ability to meet the demands of modern medicine. The purpose of this book is to describe, illustrate, and review many of the most recent developments regarding modern techniques employed in cytopathology. This latest monograph is intended for all cytologists including cytopathologists, cytotechnologists, cytology lab assistants, trainees, research scientists, and anyone who is interested in the field of cytopathology. We have invited pioneering experts in their respective fields to author these chapters. This book is not only the culmination of their groundbreaking work and effort but also presents a critical review of the current literature. We have attempted to provide readers with an informative and comprehensive aid so that they may better appreciate how emerging technology has been applied to cytology. Each chapter in this book presents a stand-alone contemporary review of emerging topics in cytopathology. We hope that you will find this monograph thought-provoking and a valuable reference for your practice.